Purification and characterization of an amyloglucosidase from an ericoid mycorrhizal fungus (Leohumicola incrustata) - O. R. Adeoyo; B. I. Pletschke; J. F. Dames (AMB Express, 2018)
Abstract This study aimed to purify and characterize amyloglucosidase (AMG) from Leohumicola incrustata. AMG was purified to homogeneity from cell-free culture filtrate of an ERM fungus grown in a modified Melin–Norkrans liquid medium. The molecular mass of the AMG was estimated to be 101 kDa by combining the results of Sephadex G-100 gel filtration, sodium dodecyl sulphate–polyacrylamide gel electrophoresis, and zymography. The K m and k cat values were 0.38 mg mL−1 and 70 s−1, respectively, using soluble starch as a substrate. The enzyme was stable at 45 °C (pH 5.0), retaining over 65% activity after a pre-incubation period of 24 h. The metal inhibition profile of the AMG showed that Mn2+ and Ca2+ enhanced activity, while it was stable to metals ions, except a few (Al3+, Co2+, Hg2+ and Cd2+) that were inhibitory at a concentration higher than 5 mM. Thin layer chromatography revealed that only glucose was produced as the product of starch hydrolysis. The amylase from L. incrustata is a glucoamylase with promising characteristics such as temperature stability over an extended period, high substrate affinity and stability to a range of chemicals. Also, this study reports for the first time the possibility of using some culturable ERM fungi to produce enzymes for the bio-economy.